An Exploratory Study of the Effects of Personalization and Authenticity in Tiktok - Baris, David Jefferson; Heruwasto, Ignatius (President University, 2023)
TikTok represents a new form of marketing communication technology due to its features and attributes. However, despite its ability to share brands’ viral content, scant research has examined TikTok as an advertising vehicle and its implications for viral advertising campaigns. Drawing on the Elaboration Likelihood Model and the concept of self-relevance, the present study explores the impact of perceived personalization and auhenticity of TikTok content on perceived convenience, viral behavioral intentions and purchase intention. The results show that the personalization of TikTok content is negatively related to perceived convenience and authenticity of TikTok content is positively related to perceived convenience. Overall, the results of this study provide new insights and practical implications for both content creator and advertiser sides.